2018
DOI: 10.1080/07391102.2018.1448303
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new benzamide inhibitor againstα-subunit of tryptophan synthase fromMycobacterium tuberculosisthrough structure-based virtual screening, anti-tuberculosis activity and molecular dynamics simulations

Abstract: Multi-drug-resistant tuberculosis and extensively drug-resistant tuberculosis has emerged as global health threat, causing millions of deaths worldwide. Identification of new drug candidates for tuberculosis (TB) by targeting novel and less explored protein targets will be invaluable for antituberculosis drug discovery. We performed structure-based virtual screening of eMolecules database against a homology model of relatively unexplored protein target: the α-subunit of tryptophan synthase (α-TRPS) from Mycoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…The final step in this pathway is catalyzed by tryptophan synthase and inhibition of this enzyme from M. tuberculosis (MtTRPS) with both previously known and novel TRPS inhibitors has been studied. [49][50][51][52][53][54] Inhibition of MtIGPS by novel compounds, however, remains largely unexplored. Yang and co-workers reported that MtIGPS is significantly inhibited by the antibiotics streptomycin, kanamycin, and geomycine.…”
Section: Inhibition Of Mtigpsmentioning
confidence: 99%
“…The final step in this pathway is catalyzed by tryptophan synthase and inhibition of this enzyme from M. tuberculosis (MtTRPS) with both previously known and novel TRPS inhibitors has been studied. [49][50][51][52][53][54] Inhibition of MtIGPS by novel compounds, however, remains largely unexplored. Yang and co-workers reported that MtIGPS is significantly inhibited by the antibiotics streptomycin, kanamycin, and geomycine.…”
Section: Inhibition Of Mtigpsmentioning
confidence: 99%
“…9 Because a functional tryptophan synthase (TRPS) is required for the survival of bacteria in vivo and higher animals and humans do not have comparable L-Trp biosynthetic machinery, RPS is a highly specific drug target. 6,[10][11][12][13] Our study focused on inhibiting the function of TRPS, a bienzyme complex that catalyzes the last two steps of tryptophan biosynthesis. TRPS is a heterodimer, but in a biological setting, it exists as a tetramer, and the two dimers connect linearly with two β subunits attached to each other (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, benzamide C2 exerts complete bactericidal activity of Mtb H37Rv at 25 μg/ml and partial inhibition of bacterial growth at 6 μg/ml concentrations. The inhibitor associates with binding pocket of trpA at R221 through formation of hydrogen bonds 13 …”
Section: Enzymes Of Amino Acid Metabolism As Drug Targetsmentioning
confidence: 99%